The Layers of The Onion: The Impact of Satirical News on Affect and Online Sharing Behaviors. (June 2019) - Stevens, Elise M.; McIntyre, Karen
The Onion is a satirical news site that has been growing in popularity over the last two decades. Based on theories in affect and social sharing, the current studies examined the impact of this online satirical news to understand its impact on affective states and online sharing. In Study 1, participants ( N = 147) either viewed a satirical or serious (frame) news story and then were asked about affective states and sharing behaviors. In Study 2, participants ( N = 143) viewed one of the two frames but on Instagram. In Study 1, results showed that serious news stories increased both positive and negative affect. Only positive affect mediated the relationship between frame and sharing. In Study 2, results showed that satirical Instagram posts were positively associated with negative affect, which mediated the relationship between frame and sharing. This study shows the important implications of online satirical news and illuminates how different platforms can affect audiences.